LEIQ™ as an emotion and importance model for QoL: fundamentals and case studies - Anitawati Mohd Lokman; Shamsiah Abd Kadir; Saidatul Rahah Hamidi; Shuhaida Mohamed Shuhidan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Past literature has increasingly highlighted the importance of understanding people’s emotional responses towards the characteristics of everything that has points of interactions with the people. Ever since it was introduced, research relating the emotional responses to the economic power of industrial products, hospitality services, as well as employees’ or peoples’ productivity has been expanding. This paper presents a model called Lokman’s Emotion and Importance Quadrant (LEIQ)™, which was built based on axes of emotion vs. importance, to investigate emotion and the importance of the influential factors of the emotion. The paper presents two case studies; i) Employee’s Happiness, ii) Student’s Well-being, with the implementation of LEIQ™ to showcase the process to discover the indicators that affect people’s emotion, and its importance to the people in the effort to provide information to the leaders or management advocates for their strategic decision-making in ensuring well-being and Quality of Life (QoL). Both case studies have enabled the research to understand factors that affect Employee’s Happiness and Student’s Well-being, and how it is important to them. The effective use of this model could facilitate decision makers in an organisation, community, society, and even a nation at large to gain knowledge and devise correct strategies to boost people’s well-being, promoting more positive emotion, and ultimately upsurge productivity and QoL of the people.